Body mass index patterns following dysvascular lower extremity amputation - Rosenberg, Dori E. (Disabil Rehabil, 2012)
PURPOSE: Using preliminary data, we examined: (i) patterns of body mass index (BMI) over the year following amputation by amputation level and (ii) the association between BMI and mobility and prosthetic device use. METHOD: Patients from three medical centers undergoing dysvascular amputation (N = 87; M age = 62) participated in interviews pre-surgically and at 6 weeks, 4 months, and 12 months following amputation. The main outcome was self-reported BMI, adjusting for limb weight lost due to amputation. Additional outcomes were mobility and time spent using and walking in a prosthetic device. RESULTS: Adjusted BMI slightly decreased at 6 weeks (pre-surgery M = 31.2; 6 weeks M = 30.3) and 4 months (M = 30.7) but exceeded baseline levels by 12 months (M = 31.7). There were no significant BMI differences by amputation level. In multivariable analyses, higher pre-surgical BMI was associated with fewer hours of prosthetic device walking at month 4 (β = −0.49) and poorer overall mobility at month 12 (β = −0.22). CONCLUSIONS: BMI increased at one year following amputation surgery. Higher pre-surgical BMI was associated with poorer mobility and prosthetic device use. Interventions are needed to prevent excess weight gain in the year following amputation.